Bio-template assisted solvothermal synthesis of broom-like BaTiO3: Nd3+ hierarchical architectures for display and forensic applications. (June 2018) - Dhanalakshmi, M.; Nagabhushana, H.; Sharma, S.C.; Basavaraj, R.B.; Darshan, G.P.; Kavyashree, D.
Graphical abstract: Highlights: Broom-like BaTiO3 :Nd 3+ structures were prepared by solvothermal route using CTAB surfactant. Morphologies were highly dependent on temperature, pH, surfactant concentration and time durations. LFPs were visualized on various porous and non-porous surfaces. Photometric studies were carried out for display applications. Abstract: Broom-like hierarchical structures of BaTiO3 :Nd 3+ (1–11 mol %) nanophosphors (NPs) were fabricated via CTAB assisted solvothermal route. Controlled experiments namely, reaction temperature, surfactant concentration, pH and time duration were performed and its influences on morphology of the product was investigated. These conditions may tune the simple structures to broom-like hierarchical structures. The energy band gap (Eg ) of the synthesized NPs were estimated to be ∼3.29–3.42 eV. Judd–Ofelt (J–O) intensity parameters were calculated by utilizing the photoluminescence emission spectra instead of normal absorption spectra. The CIE and CCT results indicates that the NPs exhibit intense blue light applicable for fabrication of cool LEDs. LFPs visualized by staining optimized NPs following powder dusting technique exhibits well defined level 1–3 ridge characteristics. Hence, it evidences versatility of the development techniques and NPs for visualization of LFPs with excellent sensitivity, selectivity, and without background hindrance. The obtained results evidence that the optimized NPs can be explored as a novel labeling marker for probing visualization of LFPs and solid state lightning.